Practicum - A space for leadership and mentoring - Debbie Woolston; Tracy Dayman (New Zealand Journal of Teachers' Work)
Associate teachers (AT) play a crucial role in supporting beginning teachers but there is little research that identifies the practicum as an opportunity for advancing ATs’ leadership capability. While research identifies mentoring as central to the way ATs support beginning teachers entering the profession, there is little explicit discussion of the leadership skills ATs engage in and model to student teachers during a practicum experience. Nor is there explicit acknowledgement of the AT role as a pathway to leadership for early childhood educators.